WE6.9 Enoxaparin venous thromboembolism prophylaxis in bariatric surgery: A best evidence topic update. (9th August 2022) - Pathmaraj, Bavin; Parmar, Chetan; Sufi, Pratik
Abstract: Aim: To examine the literature and identify the best dosing regimen of enoxaparin for perioperative venous thromboembolism (VTE) prophylaxis in patients undergoing bariatric surgery. This presentation reviewed publications from 2015 to 2021 to determine whether previous recommendations based on a similar examination of evidence conducted in 2015 needed to be updated, considering new evidence. Method: A literature search was conducted in accordance with a structured format. One hundred and one papers were identified using a standardised literature search from 2015 to 2021 on Medline and EMBASE using the same search terms "bariatric surgery" AND "venous thromboembolism" AND "enoxaparin". The author, date and country of publication, patient groups and VTE prophylaxis strategy, level of evidence, outcomes, key results and study weaknesses were tabulated. Results: Three studies were selected as the best available evidence to answer the question. All three articles were non-randomised cohort studies analysing VTE and major bleeding rates following different bariatric thromboprophylaxis regimens. There was still no level 1 evidence available to answer this question. Conclusion: Enoxaparin 40mg/day starting 12 hours after the operation, continuing for at least one week post-discharge may be the best enoxaparin dosing regimen for VTE prophylaxis in bariatric surgery patients based on the best evidence available to 2021. New evidence suggests that the previously recommended 40mg enoxaparin twice daily for in-hospital patients may increase major bleeding risk. A Randomised Controlled Trial would probably require 3500 patients in each arm to identify the best enoxaparin dosing regimen.